Building an electronic resource collection : a practical guide - Lee, Stuart D.; Boyle, Frances (London : Facet, 2004)
"This guide identifies best practice and highlights the pitfalls involved in building an electronic resource collection, and the case studies and models used are fully international in their application. This is an essential book for the professional or student new to e-collection development, as well as for the experienced practitioner."--Jacket.
1. Preliminary issues -- 2. What is an offer? : the electronic resources landscape -- 3. E-books and e-journals -- 4. What to buy? : assessing and acquiring the electronic resource -- 5. Delivering the electronic resource.
Previous edition: Library Association Publishing, 2002.
Includes bibliographical references (pages 152-164) and index.
NLJCols20082021
Keywords: Digital libraries; Biblioth eques virtuelles; Biblioth eque electronique; Acquisitions documentaires; Digital libraries; Electronic documents; Virtual libraries; Elektronische informatie; Collectievorming; Digitale bibliotheken; Biblioth eques -- Ressources Internet; Biblioth eques -- Acquisitions -- Ressources Internet; Biblioth eques -- Fonds sp eciaux -- Information electronique; Biblioth eque virtuelle; Gestion de l'information.; Information electronique; Elektroniska resurser; Best andsutveckling (bibliotek); Guide (Descripteur de forme)